Roles and responsibilities of student nurses/clinical staff towards clinical teaching and learning at Limpopo College of Nursing -Sovenga Campus - Dilebo, Matete Enia (My University, 2014)
The clinical learning environment is a complex social entity that influences student learning outcomes in the clinical real life setting. The purpose of this study was to examine the roles and responsibilities of student nurses / clinical staff towards clinical teaching during their clinical experiences. Examination of these roles and responsibilities of student nurses / clinical staff towards clinical teaching and learning give insight into the educational functioning of the clinical areas and allows nurse educators to enhance students' opportunities for learning. Quantitative, non-experimental, descriptive design was used. Data was collected by means of the self-administered questionnaires. Data was analyzed using SPSS Version 18. Students consistently ranked the ability of clinicians to teach lowest even though they have enough experience and qualifications. The conclusions drawn from this study supported the assumptions that the quality and success of the clinical experience depends largely on the individual nurse's attitude, willingness and ability to facilitate teaching and learning opportunities in a supportive way. Positive ratings for students was that 42 (84.0%) were cooperative while few students 8 (16.0%) were not cooperative, 26 (52.0%) were committed to learning, 31 (62.0%) always had clinical workbooks/registers, while negative reports were that only 11 (22.0%) of students were not punctual, 17 (36.0%) participated actively in clinical activities and 16 (32.0%) were not displaying critical thinking. Recommendations emanating from this study included: development of strategies that will strengthen collaboration between the nursing college and the clinical staff to promote the value and acceptance of students in clinical area as part of the team, motivation of more professional nurses to study Nursing Education, student nurses to be actively involved in clinical activities, improvement on student supervision, and delegation of duties according to learning needs.
MCur
Department of Advanced Nursing Science
Keywords: Student; UCTD; Nurses; Clinical; Staff; Teaching; 610.730690968256; Nursing students -- South Africa -- Limpopo; Nursing --Study and teaching -- South Africa -- Limpopo; Medical education -- South Africa -- Limpopo